Mesopause dynamics from the scandinavian triangle of radars within the PSMOS-DATAR Project. - Hall, Chris; Manson, A.H.; Meek, C.E.; Nozawa, S.; Mitchell, N.J.; Pancheva, D.; Singer, W.; Hoffmann, P. (European Geosciences Union, 2004)
The "Scandinavian Triangle" is a unique trio of radars within the DATAR Project (Dynamics and Temperatures from the Arctic MLT (60–97km) region): Andenes MF radar (69°N, 16°E); Tromsø MF radar (70°N, 19°E) and Esrange "Meteor" radar (68°N, 21°E). The radar-spacings range from 125-270km, making it unique for studies of wind variability associated with small-scale waves, comparisons of large-scale waves measured over small spacings, and for comparisons of winds from different radar systems. As such it complements results from arrays having spacings of 25km and 500km that have been located near Saskatoon. Correlation analysis is used to demonstrate a speed bias (MF smaller than the Meteor) between the radar types, which varies with season and altitude. Annual climatologies for the year 2000 of mean winds, solar tides, planetary and gravity waves are presented, and show indications of significant spatial variability across the Triangle and of differences in wave characteristics from middle latitudes.